Analyzing Consumer Reviews with Text Mining Approach: A Case Study on Samsung Galaxy S3. Issue 1 (June 2016) - Dasgupta, Subhasis; Sengupta, Kalyan
In the era of Internet, it is not necessary to run an expensive market survey to explore what the users are saying about a product and to find out whether there are any modifications required within the product. There are several sites available where users from different parts of the world post their comments after using a product. These comments can be analyzed scientifically through text mining to understand how the users have used different words in relation to the said product. The current study has been focused at finding out the word association with Samsung Galaxy 3 (a high-end smart phone). It also deals with how a few keywords are related to other words through correlation analysis.